Thymol as Biofilm and Efflux Pump Inhibitor: A Dual‐Action Approach to Combat Mycobacterium tuberculosis - Shankar Das, Bhabani; Sarangi, Ashirbad; Pahuja, Isha; Singh, Vishal; Ojha, Suvendu; Giri, Sidhartha; Bhaskar, Ashima; Bhattacharya, Debapriya (Cell biochemistry and function, 2024)
ABSTRACT Tuberculosis (TB) remains a significant global health challenge, exacerbated by the emergence of drug‐resistant strains of Mycobacterium tuberculosis (M. tb). The complex biology of M. tb, particularly its key porins, contributes to its resilience against conventional treatments, highlighting the exploration of innovative therapeutic strategies. Following with this challenges, the present study investigates the bioactivity properties of phenolic compounds derived from the terpene groups, specifically through Thymol (THY) against M. smegmatis as a surrogated model for M. tb. Furthermore, the study employed with combination of two approaches i.e., in vitro assays and computational methods to evaluate the efficacy of THY against M. smegmatis and its interaction with M. tb biofilm and efflux pump proteins, particularly Rv1258c and Rv0194. The in vitro findings demonstrated that THY exhibits inhibitory activity against M. smegmatis and shows promising interaction with a combination of isoniazid (INH) and rifampicin (RIF) of TB regimens. Furthermore, THY demonstrated significant inhibitory action towards motility and biofilm formation of M. smegmatis. The combination of THY with INH and RIF exhibited a synergistic effect, enhancing the overall antimicrobial efficacy. Additionally, THY displayed reactive oxygen species (ROS) activity and potential efflux pump inhibitory action towards M. smegmatis. The computational analysis revealed that THY interacts effectively with efflux pump proteins Rv1258c and Rv0194, showing superior binding affinity compared to verapamil, a known efflux pump inhibitor. Pharmacokinetic studies highlighted that THY possess a favourable safety profile. In conclusion, THY represents a promising inhibitory compound for tuberculosis prevention, potentially addressing challenges posed by drug resistance. Summary This study investigates the bioactivity properties of Thymol (THY) against Mycobacterium smegmatis and its potential as a therapeutic agent. THY diminished bacterial motility and led to a 95% reduction in biofilm formation, revealing its synergistic effects alongside INH and RIF. THY was effective in reducing dormant and persistent cells found in biofilms, with its inhibition mechanisms associated with the modulation of efflux pumps and the production of reactive oxygen species (ROS). Computational analysis highlights a way of THY's efflux pump inhibitory and antibiofilm activity action with Rv1258c and Rv0194 proteins. The significance of this study opens up a key window to provide a novel solution towards the growing problem of drug‐resistant TB, which remains a major global health challenge.